Humanization of care in pediatric wards: differences between perceptions of users and staff according to department type - Mandato, C. (Ital J Pediatr, 2020)
BACKGROUND: As the quality and quantity of patient-centered care may be perceived differently by recipients and independent observers, assessment of humanization of pediatric care remains an elusive issue. Herein we aim to analyze differences between the degrees of verified existing vs. perceived humanization issues of a pediatric ward. Furthermore, we examine whether there is concurrence between the degrees of humanization perceived by users (parents/visitors) vs. staff members. METHODS: The study was conducted in the pediatric wards of seven medical centers of the Campania region (Italy) categorized as general (n = 4), children’s (n = 1), and university (n = 2) hospitals. The degree of existing humanization was assessed by a multidisciplinary focus group for each hospital through a pediatric care-oriented checklist specifically developed to individuate the most critical areas (i.e., those with scores < 2.5). The degree of perceived humanization was assessed through four indicators: well-being, social aspects, safety and security, and health promotion. RESULTS: The focus groups showed that critical areas common to all centers were mainly concerned with welfare, mediation, translation, and interpretation services. Specific critical issues were care and organizational processes oriented to the respect and specificity of the person and care of the relationship with the patient. Perceived humanization questionnaires revealed a lack of recreational facilities and mediation and translation services. As for specific features investigated by both tools, it was found that mediation and interpretation services were lacking in all facilities while patient perceptions and observer ratings for space, comfort, and orientation concurred only in the general hospital evaluations. CONCLUSIONS: Future humanization interventions to ensure child- and family-friendly hospital care call for careful preliminary assessments, tailored to each pediatric ward category, which should consider possible differences between perceived and verified characteristics.